EVALUATION OF THE IMPACT OF NURSE-LED INTERVENTIONS ON SURGICAL PATIENTS WITH RHEUMATOID ARTHRITIS (International Journal of Food and Nutritional Sciences, 2022)
Nursing interventions are the measures taken and the methods used by nurses to treat and care for patients. Patients' health, well-being, and rehabilitation are all affected by nursing treatments. Treatments, procedures, and drugs are all examples of nursing interventions. Nursing interventions might also include educating patients or repositioning their beds as needed. Hundreds of nursing activities are categorized as interventions by medical professionals, but a nurse just has to be an expert in the interventions that pertain to their area of practice, such as gerontological or hospice care. The Rheumatology Clinic at the Government Royapettah Hospital in the Chennai suburb of Royapetta served as the study's site. Information is gathered over a long period of time, with several data points before and after the introduction of a therapy, in the quasi-experimental non-equivalent time series design. By this paper we can improved RA self-care is possible with the help of Nurse-Led Interventions, which may be used successfully in rheumatology clinics and centers. Nurse-led interventions have been shown to enhance clinical outcomes for individuals with rheumatoid arthritis at a reasonable cost.